Sistemas domóticos - Ferreira, Miguel (2012)
Este artigo tem como principal objectivo constituir-se como um manual que permita ao cliente final conhecer as potencialidades de um sistema domótico, para assim escolher o sistema que melhor se adeqúe aos requisitos que pretende ver satisfeitos. Para isto, foram descritos as funcionalidades dos sistemas domóticos bem como os principais sistemas existentes no mercado. This article is to achieve constitute itself as a manual that allows the user to know the potential of a domotic system, so choose the system that best suits the requirements that it wants to see satisfied. For this, are described the features of the domotic systems and the main systems existing in the market.